Developing vanadium redox flow technology on a 9-kW 26-kWh industrial scale test facility: Design review and early experiments. (15th November 2018) - Guarnieri, Massimo; Trovò, Andrea; D'Anzi, Angelo; Alotto, Piergiorgio
Graphical abstract: Highlights: The potential of large VRFBs in grid fast and slow storage services are outlined. The lack of experimental data and papers on kW-scale VRFBs is highlighted. A new kW-scale VRFB test facility based on a 40-cell 600-cm 2 stack is presented. Early tests of polarization curves, power curves and efficiency are presented. 9 kW and 400 A have been achieved, with a current density of 665 mA/cm 2 . Abstract: Redox Flow Batteries (RFBs) have a strong potential for future stationary storage, in view of the rapid expansion of renewable energy sources and smart grids. Their development and future success largely depend on the research on new materials, namely electrolytic solutions, membranes and electrodes, which is typically conduced on small single cells. A vast literature on these topics already exists. However, also the technological development plays a fundamental role in view of the successful application of RFBs in large plants. Despite that, very little research is reported in literature on the technology of large RFB systems. This paper presents the design, construction and early operation of a vanadium redox flow battery test facility of industrial size, dubbed IS-VRFB, where such technologies are developed and tested. In early experiments a peak power of 8.9 kW has been achieved with a stack specific power of 77 W kg −1 . The maximum tested current density of 635 mA cm −2 has been reached with a cell voltage of 0.5 V, indicating that higher values can be obtained. The test facility is ready to be complemented with advanced diagnostic devices, including multichannel electrochemical impedance spectroscopy for studying aging and discrepancies in the cell behaviors.